2021
DOI: 10.7759/cureus.16415
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Spontaneous Pneumothorax in a COVID-19 Recovered Patient

Abstract: Coronavirus disease 2019 (COVID-19) is an infectious disease primarily affecting the lungs with a spectrum of post-viral complications. There are well-described examples of pneumonia, empyema, pneumomediastinum, and spontaneous pneumothorax cases following COVID-19 infection within the literature. However, there is insufficient evidence implicating the cause of spontaneous pneumothorax in COVID-19 recovered patients. We present a previously infected COVID-19 patient who developed a secondary spontaneous pneumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…On a cellular level, the changes of the parenchyma secondary to COVID-19 can play a role. For instance, the disruption of protein, downregulation of surfactant, loss of extracellular matrix and surfactant and hypercoagulative state can all contribute to developing pneumothorax in COVID-19 patients (7). In the present cases, we found that the presence of pneumothorax in patients with COVID-19 pneumonia can be present at any time of admission whether they were mechanically ventilated or not.…”
Section: Discussionsupporting
confidence: 52%
“…On a cellular level, the changes of the parenchyma secondary to COVID-19 can play a role. For instance, the disruption of protein, downregulation of surfactant, loss of extracellular matrix and surfactant and hypercoagulative state can all contribute to developing pneumothorax in COVID-19 patients (7). In the present cases, we found that the presence of pneumothorax in patients with COVID-19 pneumonia can be present at any time of admission whether they were mechanically ventilated or not.…”
Section: Discussionsupporting
confidence: 52%
“…Pneumothorax and pneumomediastinum were observed predominantly in our patient who had history of critical COVID-19. It was found that pneumothorax can occur in any phase of the disease and even as a late sequela after recovery from initial infection in the absence of prior pulmonary disease or barotrauma [30,31].…”
mentioning
confidence: 99%
“…One study indicated that 7.4% of post-COVID-19 patients develop pneumomediastinum, and 8.6% develop pneumothorax. [7] Although many case reports cite an increase in the rate of pneumothorax in post-COVID-19 patients, [8][9][10] data on this finding after cardiac surgery are limited. In their study evaluating the effect of COVID-19 infection on cardiac surgery outcomes, Thomas et al [5] evaluated preoperative chest computed tomography (CT) findings and detected emphysematous and fibrotic changes in 2.85% and 42.8% of patients, respectively.…”
Section: Discussionmentioning
confidence: 99%